cis- and trans-regulatory contributions to a hierarchy of factors influencing gene expression variation - Siddhant Kalra; Stephen Lanno; Guadalupe Sanchez; Joseph D. Coolon (Communications Biology)
Abstract Gene expression variation results from numerous sources including genetic, environmental, life stage, and even the environment experienced by previous generations. While the importance of each has been demonstrated in diverse organisms, their relative contributions remain understudied because few investigations have simultaneously determined each within a single experiment. Here we quantified genome-wide gene expression traits in Drosophila, quantified the contribution of multiple different sources of trait variation and determined the molecular mechanisms underlying observed variation. Our results show that there is a clear hierarchy in our data with genome and developmental stage contributing on average considerably more than current and finally previous generation environmental effects. We also determined the role of cis and trans-regulatory changes across different sources of trait variation, highlighting their importance in adaptation and environmental responses and showing unexpectedly that transgenerational effects herein were predominantly associated with changes in trans-regulation.